# Yahoo Web Search

1. Sort by

1. ### Use mathematical induction?

...now to prove true for k = 1 and k = k + 1 Consider k = 1 --------------------- LHS = 1 RHS = (2 x 3) / 6 = 1 Thus true for k = 1 Consider k...

1 Answers · Science & Mathematics · 28/03/2014

2. ### Proving trig identities questions?

...sin θ - cos θ)/sin θ][cos θ/(-(sin θ - cos θ))] = -cos θ/sin θ = -cot θ = LHS ☜ QED 2. prove (cotθ/cosθ)-cscθ = 0 LHS = (cos θ/sin θ)/cos θ...

3 Answers · Science & Mathematics · 21/03/2014

3. ### (x+5)/(2x-4) Finding derivative question?

...14+%2F+%282x+-+4%29%5E2+%5D Wolfram chooses LHS as derivative. I choose RHS. They are equivalent. In...

1 Answers · Education & Reference · 06/03/2014

It is true, since LHS = 14 mod 37 and RHS = 2 + 12 mod 37 Again, Fermat's...

2 Answers · Science & Mathematics · 24/02/2014

5. ### prove c is irrational?

...4k^2 + 4k + 1 so if a = 2k + 1 and b = 2m + 1 where m is integer, then the LHS becomes 4k^2 + 4k + 4m^2 + 4m + 2 = c^2 2(2k^2 + 2k + 2m^2 + 1) = c...

5 Answers · Science & Mathematics · 21/02/2014

6. ### cot x -1/cot x +1 = cos2 x /1+sin 2 x,how to prove it?

(cotx -1)/(cotx +1) = cos(2x) /(1+sin(2x)) LHS = (cosx/sinx - 1)/(cosx/sinx + 1) = (cosx - sinx)/sinx / (cosx + sinx)/sinx = (cosx - sinx)/(cosx...

2 Answers · Science & Mathematics · 07/02/2014

7. ### Linear Algebra: Complete the Proof?

...2+ c_2 〖λ_2〗^(n-2) 〖λ_2〗^2=c_1 〖λ_1〗^n+c_2 〖λ_2〗^n= x_n =the LHS. Initial conditions, say x_1=u,x_2=v, yield ΛC...

1 Answers · Science & Mathematics · 05/02/2014

8. ### Trig Identites (Advanced Functions 12U)?

...) / (cos Θ + sin Θ) = sec (2Θ) - tan (2Θ) work on LHS: multiply numerator and denominator by (cos Θ - sin Θ)/(cos Θ - sin...

1 Answers · Science & Mathematics · 24/01/2014

9. ### Prove: (sinxcosx)(secx)=1/sinx+cosx?

It's not true. sec(x) = 1/cos(x) so LHS = sin(x) = f(x) sin(x) does not equal 1/sin(x) + cos(x) = g(x) Or...

1 Answers · Science & Mathematics · 07/03/2014

10. ### Balance redox equation. Please review my HW?

Almost. You need one more step to get rid of the H+ and H2O on both sides of the equation. Subtract the smaller amount of both species: (Cr2O7)2- + 6H+ +2NO → 2Cr3+ + 3H2O+2NO3...

1 Answers · Science & Mathematics · 22/01/2014